PENJELIDIKAN MENGENAI TJARA PENJIMPANAN KAJU KARET (Hevea brasiliensis MA) - Balai Rayon dan Selulosa (Center for Pulp and Paper, 1965)
The effect of storage of Hevea brasiliensis MA upon the chemical composition of the wood and the pulp was studied. In this experimenc, the cooking and bleaching conditions were kept constant, but the method of srorage was varied.The growth of blue staining fungi dur